Impact of Climate Change on Dam Construction: A Review - Murdiagatma, Sefrinta Sasma (Jurnal Teknik Sipil, 2025)
Climate change is a change in climate components such as temperature, rainfall, humidity, evaporation, wind direction and speed, and air. Climate change is a big problem that affects many areas, including dam construction. Climate change affects the ecosystem within the dam, changing river flow patterns and sediment reduction, affecting riparian vegetation, changing the frequency of waterlogging and swamp connectivity, and increasing the risk of flooding and dam safety. This research aims to conduct a literature study to determine the influence of the impact of climate change on dam construction from various aspects and problems that may occur. By using a comprehensive descriptive research method to summarize the entire material of this literature study. This study produces an understanding of how climate change can affect freshwater ecosystems, and natural river flow patterns, and cause changes in temperature, precipitation, and wind patterns. The amount of sediment that falls into rivers becomes greater during the rainy season, causing potential water shortages during the dry season and flooding during the rainy season, and changes in land use due to dam construction. For this reason, it is necessary to control and manage dam construction, as well as risk mitigation so that the impact of climate change that occurs on dam construction can be avoided.